Comparative genomics of Cryptosporidium parvum reveals the emergence of an outbreak-associated population in Europe and its spread to the United States - Bellinzona, Greta; Nardi, Tiago; Castelli, Michele; Batisti Biffignandi, Gherard; Adjou, Karim; Betson, Martha; Blanchard, Yannick; Bujila, Ioana; Chalmers, Rachel; Davidson, Rebecca; D'Avino, Nicoletta; Enbom, Tuulia; et al. (Genome research, 2024)
The zoonotic parasite Cryptosporidium parvum is a global cause of gastrointestinal disease in humans and ruminants. Sequence analysis of the highly polymorphic gp60 gene enabled the classification of C. parvum isolates into multiple groups (e.g., IIa, IIc, Id) and a large number of subtypes. In Europe, subtype IIaA15G2R1 is largely predominant and has been associated with many water- and food-borne outbreaks. In this study, we generated new whole-genome sequence (WGS) data from 123 human- and ruminant-derived isolates collected in 13 European countries and included other available WGS data from Europe, Egypt, China, and the United States (n = 72) in the largest comparative genomics study to date. We applied rigorous filters to exclude mixed infections and analyzed a data set from 141 isolates from the zoonotic groups IIa (n = 119) and IId (n = 22). Based on 28,047 high-quality, biallelic genomic SNPs, we identified three distinct and strongly supported populations: Isolates from China (IId) and Egypt (IIa and IId) formed population 1; a minority of European isolates (IIa and IId) formed population 2; and the majority of European (IIa, including all IIaA15G2R1 isolates) and all isolates from the United States (IIa) clustered in population 3. Based on analyses of the population structure, population genetics, and recombination, we show that population 3 has recently emerged and expanded throughout Europe to then, possibly from the United Kingdom, reach the United States, where it also expanded. The reason(s) for the successful spread of population 3 remain elusive, although genes under selective pressure uniquely in this population were identified.